A phase II study of S-1 and cisplatin with concurrent thoracic radiotherapy followed by durvalumab for unresectable, locally advanced non-small-cell lung cancer in Japan (SAMURAI study): primary analysis. (December 2022) - Tanaka, Hisashi; Tanzawa, Shigeru; Misumi, Toshihiro; Makiguchi, Tomonori; Inaba, Megumi; Honda, Takeshi; Nakamura, Junya; Inoue, Koji; Kishikawa, Takayuki; Nakashima, Masanao; Fujiwara, Keiichi; Kohyama, Tadashi; et al.
Background: The standard of care for unresectable, locally advanced non-small-cell lung cancer (LA-NSCLC) is chemoradiotherapy (CRT) followed by durvalumab, based on the PACIFIC study. Although multiple Japanese phase II studies have shown high efficacy and tolerability of CRT with cisplatin plus S-1 (SP), no prospective study using durvalumab after SP-based CRT has been reported. Objectives: We conducted a multicenter phase II study of this approach, the interim analysis of which showed a high transition rate to durvalumab consolidation therapy. Here, we report the primary analysis results. Design: In treatment-naïve LA-NSCLC, cisplatin (60 mg/m 2, day 1) and S-1 (80–120 mg/body, days 1–14) were administered with two 4-week cycles with concurrent thoracic radiotherapy (60 Gy) followed by durvalumab (10 mg/kg) every 2 weeks for up to 1 year. Methods: The primary endpoint was 1-year progression-free survival (PFS). The expected 1-year PFS and its lower limit of the 80% confidence interval (CI) were set as 63% and 47%, respectively, based on the results of TORG1018 study. Results: In all, 59 patients were enrolled, with 51 (86.4%) proceeding to durvalumab. The objective response rate throughout the study was 72.9% (95% CI: 59.7–83.6%). After median follow-up of 21.9 months, neither median PFS nor OS was reached. The 1-year PFS was 72.5% (80% CI: 64.2–79.2%, 95% CI: 59.1–82.2%), while the 1-year overall survival was 91.5% (95% CI: 80.8–96.4%). No grade 5 adverse events were observed throughout the study. The most common adverse event during the consolidation phase was pneumonitis (any grade, 78.4%; grade ⩾3, 2.0%). Eventually, 52.5% of patients completed 1-year durvalumab consolidation therapy from CRT initiation. Conclusion: This study of durvalumab after SP-based CRT met its primary endpoint and found a 1-year PFS of 73% from CRT initiation. This study provides the first prospective data on the prognosis and tolerability of durvalumab consolidation from the initiation of CRT. Trial registration: Japan Registry of Clinical Trials, jRCTs031190127, registered 1 November, 2019, https://jrct.niph.go.jp/latest-detail/jRCTs031190127